Paradigms of safety of classical and autonomous shipping - Mulina, Elena Vadimovna; Ermakov, Sergey Vladimirovich (Вопросы безопасности, 2025)
The subject of the study is the evolution of the paradigm of shipping safety. The purpose of the study is linguistic formalization and comparative analysis of the existing paradigm of classical shipping safety and a hypothetical paradigm of autonomous shipping safety, taking into account the evolutionary change of paradigms. The paper defines such concepts as shipping safety, shipping safety paradigm. The modern paradigm of classical shipping safety is analyzed by four safety objects. It is revealed that in this paradigm a human is the main and only safety object. It is shown that the modern paradigm of shipping safety is externally positioned as based on a set of many regulatory requirements, but in fact it is based on the natural sense of self-preservation, rational thinking, will, experience and knowledge of the crew members of vessels. The possible evolution of the shipping safety paradigm in the context of the development of the autonomous shipping is described. Some problems of this evolution are identified: the chaos of current methodologies, errors in remote assessment of the situation by an external captain, the psychological problem of interaction between classical ships with crews and autonomous ships. It is shown that a human in the paradigm of autonomous shipping safety will be naturally excluded from the number of safety objects, while the number of such objects will be replenished with information and technology, and the dangers to the ship and the environment will be less critical. The novelty of the study lies in the paradigmatic approach to the study of shipping safety, in the substantiation of the stages of development of autonomous shipping and the paradigm of its safety, as well as in the final structure of the hypothetical paradigm of autonomous shipping safety.